Kebijakan Pendidikan Islam Berbasis Motto Daerah â€œBersujudâ€ di Kabupaten Tanah Bumbu Kalimantan Selatan - Rusdiansyah, Rusdiansyah (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The presence of a motto is not just a word sweetener. But it must have meaning that can be implemented in a concrete form. The values of Islamic education contained in the prostration motto can be implemented in the form of policies by the government as the formulator of the motto. So, it becomes a necessity if the motto